Exploring the levels of work fatigue among rice farmers: A Cross-sectional study in an agricultural area - Nurfika Asmaningrum; Angelina Paramitha Astuti Dos Santos; Dodi Wijaya; Retno Purwandari; Kholid Rosyidi Muhammad Nur (KHD-Production, 2025)
The agriculture sector plays an important role in a country's economy, and one of the important sectors is food crops such as rice. Agricultural activities can put farm workers at risk of work-related accidents, and one of the factors that influences this is work fatigue. Work fatigue is the body's defense mechanism to reduce more severe damage when someone does excessive activity. This research analyzed work fatigue among farmers in Antirogo village, Sumbersari District, Jember Regency. This research was quantitative descriptive research using a sampling method on 290 respondents. This research was conducted using univariate analysis with frequency distribution. This research collected data using the Swedish Occupational Fatigue Inventory (SOFI) questionnaire. Data collection results showed that the highest result of assessment indicators in the medium category for lack of energy was 68.3%. Exertion of physical exertion was 62.4%, and physical discomfort was 46.6%; the lowest results were found in a mild category: motivation at 89.7% and sleepiness at 60%. The overall results of work fatigue among rice farmers in Antirogo Village are in the medium category of 60%. The bivariate analysis showed a meaningful relationship between the characteristics of the respondents, gender, and working period to the occurrence of work fatigue among rice farmers in Antirogo Village. This research showed that rice farmers experience fatigue influenced by the work environment and having good motivation can reduce fatigue.